Association of leukocyte elastase in semen and seminal plasma with sperm parameters and pregnancy outcomes in male fertility - Mausumi Das; Maha Gumssani; Julia Mullaney; Ralf Henkel; Suks Minhas; Marie Claire Aquilina; Channa N Jayasena (Endocrine Connections)
Background: Semen analysis is the standard test for evaluating male fertility. However, it may not address all aspects of male infertility. This review explores the role of leukocyte elastase (LE) as a possible biomarker for male fertility by evaluating 28 corresponding studies. Objectives: We aimed to explore how LE levels in semen relate to sperm quality and pregnancy outcomes. Methods: This systematic review followed PRISMA guidelines and included studies from PubMed, Medline, Embase and Scopus (March 22–25, 2024) using the keywords ‘elastase’, ‘sperm’ and ‘semen’. Out of 897 identified articles, 334 were screened, leading to 90 full-text reviews. We included 28 studies reporting sperm parameters linked to LE and excluded non-English articles, reviews and animal studies. Data collected included study details, methods, population, LE levels, sperm characteristics and pregnancy outcomes. A narrative synthesis was used because of differing study designs. Quality assessment, using the National Heart, Lung, and Blood Institute tool, rated 21 studies medium quality, 6 high and 1 low. Results: Only a limited number of studies reported a correlation between LE levels and sperm parameters, with no significant link to sperm concentration. Overall, we did not identify a strong association between LE levels and pregnancy or fertilization rates. Conclusions: Although LE serves as a marker for seminal leukocyte concentration, its link to sperm quality and fertility outcomes remains weak and inconsistent. Based on current evidence, LE does not appear to be a reliable diagnostic marker for male infertility. Future studies should focus on standardizing LE measurement techniques and exploring its interaction with other semen parameters to clarify its role in male fertility.